PERAN DUKUNGAN KELUARGA TERHADAP MANAJEMEN STRES PADA PASIEN GAGAL GINJAL DI YOGYAKARTA - Basirun Basirun; Hafsah Budi Argiati (Universitas Sarjanawiyata Tamansiswa, 2015)
ABSTRACTThe purpose of this research is to determined stress management for renal failure patient at the role of family’s support. Furthemore, this research also aims to uncover more about problems that can be caused by renal failure. Subjects in this research is men and women who have renal failure. Subjects feel worry, fearfull and confused because worry about their future. This research using the techniques of data collection using inteviews and observation. The result of the role of family’s support at stress management for renal failure patient is patient make a choise to compose oneself with pray to God. In general, when renal failure patient heard that they diagnosed by doctor they feel stress, but subject’s family give participant and support any time. Keywords: The role of Family’s Support, Stress Management, Renal Failure Patient